2017
DOI: 10.1037/xlm0000422
|View full text |Cite
|
Sign up to set email alerts
|

The role of familiarity in correcting inaccurate information.

Abstract: People frequently continue to use inaccurate information in their reasoning even after a credible retraction has been presented. This phenomenon is often referred to as the continued influence effect of misinformation. The repetition of the original misconception within a retraction could contribute to this phenomenon, as it could inadvertently make the "myth" more familiar-and familiar information is more likely to be accepted as true. From a dual-process perspective, familiarity-based acceptance of myths is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
232
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(268 citation statements)
references
References 79 publications
27
232
3
6
Order By: Relevance
“…Further, compared with post warnings, a correction repeats the misinformation—a quality that Lewandowsky predicted may reinforce the misinformation and result in a backfire effect. Consistent with recent work using the continued influence effect paradigm (Ecker et al, ; Swire, Ecker, & Lewandowsky, ), we found no support for such a backfire effect here, suggesting that concern over backfire effects based on restatement alone are, perhaps, unwarranted.…”
Section: Discussionsupporting
confidence: 83%
“…Further, compared with post warnings, a correction repeats the misinformation—a quality that Lewandowsky predicted may reinforce the misinformation and result in a backfire effect. Consistent with recent work using the continued influence effect paradigm (Ecker et al, ; Swire, Ecker, & Lewandowsky, ), we found no support for such a backfire effect here, suggesting that concern over backfire effects based on restatement alone are, perhaps, unwarranted.…”
Section: Discussionsupporting
confidence: 83%
“…However, reminders should also become a source of interference when change is detected but not recollected (cf. Swire, Ecker, & Lewandowsky, 2017), due to the increased accessibility of List 1 pairs. Critically, these effects should depend on the extent to which reminders cue retrieval of existing memories.…”
Section: The Present Studymentioning
confidence: 99%
“…From a theoretical point of view, some have argued that repeating misinformation in this manner should be avoided because such corrections increase the misinformation's familiarity, which might have undesired consequences: The more familiar information is, the easier it is retrieved from memory, and the more likely it is accepted as true (Dechêne, Stahl, Hansen, & Wanke, ; Weaver, Garcia, Schwarz, & Miller, ); thus, boosting misinformation familiarity might counteract and offset the intended effect of the correction, potentially even leading to ironic backfire effects (Lewandowsky et al ., ; Peter & Koch, ; Skurnik, Yoon, Park, & Schwarz, ; also see Swire, Ecker, & Lewandowsky, ). Moreover, if communication recipients have not encountered a particular false claim before, such corrections can familiarize them with misinformation they were not yet familiar with.…”
Section: Introductionmentioning
confidence: 98%